Keuntungan Usahatani Kopi Arabika di Desa Catur, Kecematan Kintamani, Kabupaten Bangli - Cening Kardi; Luh Putu Kirana Pratiwi; I Made Tamba; Dedi Yane Kadiwano (AGRIMETA : Jurnal Pertanian Berbasis Keseimbangan Ekosistem, 2024)
The cultivation of Arabica coffee plays a strategic role in supporting the economy of farmers in Catur Village, Kintamani District, Bangli Regency, which is one of the centers for quality coffee production in Bali. This study aims to analyze production costs, profits, and the influence of production factors on the profits of Arabica coffee farming in farmer groups in Catur Village. The analysis method used in this research is the Cobb-Douglas multiple linear regression method. The analysis results show that the average production cost of Arabica coffee is Rp14,755,930 per 81 are of farmland per year, with a profit reaching Rp48,924,070 per year. The farming efficiency, measured through the R/C Ratio of 4.32, indicates that Arabica coffee farming in the research location is feasible for development. The production factor significantly affecting profits is NPK fertilizer, with a positive elasticity (1.060), while urea fertilizer has a negative impact on profits (-0.305). Therefore, proper fertilizer use and good farm management are essential to increase profits. Farmers are advised to optimize the use of NPK fertilizer and control the dosage of urea fertilizer to maximize productivity and farming efficiency for Arabica coffee